ZnO / polymer junction growth for hybrid solar cell applications - Mohamad, Souad A. (IIUM Press, 2011)

(untitled)
A hybrid solar cell is designed and proposed as a feasible and reasonable alternative. With the employment of zinc oxide (ZnO) and polyethylene oxide (PEO) thin films. ITO based thin films of ZnO were deposited by sputtering technique and ITO based thin films of polyethylene were deposited by solution cast technique and used as an active polymer blend. These ITO base thin films were introduced with ZnO and PEO in such a way that, the most effective configuration was optimized to be Ag/ITO/ZnO/PEO/ITO/Ag. All thin films samples were subjected to structural, optical and morphological characterization by; X-Ray, UV-VIS and SEM respectively.